Photographing crime scenes in twentieth-century London: microhistories of domestic murder - Neale, Alexa (History of crime, deviance and punishment, 2020)
"How can we read crime scenes through photography? Making use of micro-histories of domestic murder and crime scene photographs made available for the first time, Alexa Neale provides a highly original exploration of what crime scenes can tell us about the significance of expectations of domesticity, class, gender, race, privacy and relationships in twentieth-century Britain. With 10 case studies and 30 black and white images, Photographing Crime Scenes in 20th-Century London will take you inside the homes that were murder crime scenes to read their geographical and symbolic meanings in the light of the development of crime scene photography, forensic analysis and psychological testing. In doing so, it reveals how photographs of domestic objects and spaces were often used to recreate a narrative for the murder based on the defendant's perceived identity rather than to prove if they committed the crime at all. Bringing the history of crime, British social and cultural history and the history of forensic photography to the analysis of the crime scene, this study offers fascinating details on the changing public and private lives of Londoners in the 20th century"--